Specific factors and financial performance of domestic licensed commercial banks in Sri Lanka - Jeyan Suganya, D.F.; Kengatharan, L. (My University, 2018)
This study investigated to what extent bank specific factors impact on financial performance of domestic licensed commercial banks in Sri Lanka. Explanatory variables of this study were capital adequacy ratio, operating cost efficiency, non-performing loans, bank size and liquidity. Return on assets and return on equity were treated as criterion variables to measure financial performance. The researchers collected data from published financial statements of nine domestic licensed commercial banks listed on Colombo Stock Exchange for the period of ten years from 2006 to 2015. Descriptive and inferential statistics have been used to examine the impact of bank specific factors on financial performance using STATA package. The Result of the study showed that capital adequacy ratio had positive significant impact on ROA while operating cost efficiency and non-performing loans had negative significant impact on ROA. Non-performing loans had significant negative impact on ROE while bank size had positive significant impact on ROE. However, liquidity didn't have any impact on ROA and ROE. The findings of this study may help major stakeholders of the bank to make important decisions for enhancing profitability of the bank
Keywords: Capital adequacy ratio; Operating cost efficiency; Non-performing loans; Liquidity; Net profit margin